2014
DOI: 10.1371/journal.pone.0103813
|View full text |Cite
|
Sign up to set email alerts
|

Selection Signatures in Worldwide Sheep Populations

Abstract: The diversity of populations in domestic species offers great opportunities to study genome response to selection. The recently published Sheep HapMap dataset is a great example of characterization of the world wide genetic diversity in sheep. In this study, we re-analyzed the Sheep HapMap dataset to identify selection signatures in worldwide sheep populations. Compared to previous analyses, we made use of statistical methods that (i) take account of the hierarchical structure of sheep populations, (ii) make u… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

9
154
0
4

Year Published

2016
2016
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 140 publications
(167 citation statements)
references
References 57 publications
9
154
0
4
Order By: Relevance
“…Correspondingly, we detected several genes located in the selection regions or containing unique function-altering mutations with potential relationship with adaption such as the genes in Table 1. In the precious research, the selection near the TRPM8 gene was reported to be related to adaptation to cold climate [26] and this gene also showed selection evidence in this study. The adaption process is complex and the potential role of many selection signatures in the adaptation of sheep breeds remains unclear.…”
Section: Discussionsupporting
confidence: 75%
See 4 more Smart Citations
“…Correspondingly, we detected several genes located in the selection regions or containing unique function-altering mutations with potential relationship with adaption such as the genes in Table 1. In the precious research, the selection near the TRPM8 gene was reported to be related to adaptation to cold climate [26] and this gene also showed selection evidence in this study. The adaption process is complex and the potential role of many selection signatures in the adaptation of sheep breeds remains unclear.…”
Section: Discussionsupporting
confidence: 75%
“…In the former group one conspicuous cluster related to reproduction; 59 genes belonged to this category (13 genes were related to single fertilization and 24 genes were related to spermatogenesis). Another conspicuous cluster with 284 genes was related to response to stimulus (Table 1 and Additional file 6: Table S5); one of these genes TRPM8 has been shown to be a major determinant of cold perception in the mouse [25] and was reported to be related to adaptation to cold climate on sheep [26]; 12 of the 284 genes were related to response to light stimulus and we suggested these genes might had potential relationship with seasonal estrous. In the latter group one conspicuous cluster related to reproduction as well; 15 genes belonged to this category (12 genes were related to spermatogenesis).…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations